PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH ASURANSI JIWA PADA MASA PANDEMI COVID-19 (STUDI KASUS PT ASURANSI JIWA SYARIAH BUMI PUTERA CABANG MEDAN) - Dita Marisa; Tuti Anggraini; Rahmi Syahriza (EKSYA : Jurnal Ekonomi Syariah, 2023)
This study aims to determine the effect of service quality on life insurance customer satisfaction during the Covid-19 pandemic (a case study of PT Asuransi Jiwa Syariah Bumiputera Medan Branch), with a sample size of 88 customers. The type of data used in this research is quantitative data. The data collection technique used is through a questionnaire. Analysis prerequisite tests include normality test, multicollinearity test, and heteroscedasticity test. Data analysis techniques using the t test, f test, multiple linear regression and test the coefficient of determination.The results showed that (1) there was a positive and significant effect of Tangible indicators on Customer Satisfaction of Life Insurance PT Asuransi Jiwa Syariah Bumiputera Medan Branch of 29.2%, (2) there was a positive and significant effect of Guarantee indicators on Customer Satisfaction of Life Insurance of PT Asuransi Jiwa Bumiputera Sharia Medan Branch of 37.9%, (3) there is a positive and significant effect of the Empaty indicator on Life Insurance Customer Satisfaction PT Asuransi Jiwa Syariah Bumiputera Medan Branch of 33.8%, (4) no significant effect on the Reliability indicator on Customer Satisfaction Life Insurance PT Asuransi Jiwa Syariah Bumiputera Medan Branch of -0.99%, (5) does not significantly influence the response indicator to Customer Satisfaction Life Insurance PT Asuransi Jiwa Syariah Bumiputera Medan Branch -0.33% (6) there is a positive and significant influence Tangible Evidence, Reliability, Response, Guarantee, and Empathy for Life Insurance Customer Satisfaction During the Covid-19 Pandemic PT Asuransi Jiwa Syariah Bumiputera Medan Branch with Fhitung 34,901.